The pastoral church as a space for healing and reconciliation - Thesnaar, CH (Nederduitse Gereformeerde Teologiese Tydskrif, 2012)
People experience healing and reconciliation in spaces outside of their congregations. This causes them to grapple with the question: Why they do not experience healing and reconciliation within their own local congregations? Another important question people raise is: What is pastoral about pastoral counselling? Both these questions indicate that congregational leaders and the congregations itself are struggling to create spaces within their ministry to assist people in need of healing and reconciliation. This contribution will therefore try to indicate whether pastoral care and counselling are experiencing an identity crisis in terms of its calling. I will further argue that it is essential for a pastoral theology to be rooted in theology. Link to this I will share some thoughts on the congregation as a space for healing and reconciliation.